A systematic review of the techno-economic assessment of various hydrogen production methods of power generation - Zulfhazli,; Keeley, Alexander Ryota; Takeda, Shutaro; Managi, Shunsuke (Frontiers in Sustainability, 2022)
Hydrogen is a low or zero-carbon energy source that is considered the most promising and potential energy carrier of the future. In this study, the energy sources, feedstocks, and various methods of hydrogen production from power plants are comparatively investigated in detail. In addition, this study presents an economic assessment to evaluate cost-effectiveness based on different economic indicators, including sensitivity analysis and uncertainty analysis. Proton exchange membrane fuel cell (PEMFC) technology has the most potential to be developed compared to several other technologies. PEMFCs have been widely used in various fields and have advantages (i.e., start-up, zero-emissions, high power density). Among the various sources of uncertainty in the sensitivity analysis, the cost estimation method shows inflationary deviations from the proposed cost of capital. This is due to the selection process and untested technology. In addition, the cost of electricity and raw materials, as the main factors that are unpredictable